ARAHAN LOKASI RELOKASI MASYARAKAT UNTUK MITIGASI BENCANA TSUNAMI DI KOTA PADANG - Mariati, Heny; Putri, Desi Eka; Tresia, Intan Mastura; Osronita, Osronita; Febrianto, Hary (NUCLEUS, 2024)
This study aims to identification the availability of vacant land in the city of Padang, analyze the availability of vacant land that is safe from the tsunami disaster for direction of community relocation locations in the city of Padang, integrate the availability of vacant land that is safe from the tsunami disaster for aragan the location of community relocation to the Padang City Spatial Plan, and Making a map of the direction of the community relocation location for tsunami disaster mitigation in Padang City. The sample of this research was determined according to the research topic by using the Cluster sampling technique (sample area). The data management of this research uses observation method or satellite image interpretation technique and overlay method. The results show that the availability of vacant land which will be used as a relocation location for the people of Padang City for tsunami disaster mitigation with an area of 2.73 Ha or 1.12% of the area of Padang City and can accommodate as many as ±10,238 people based on the average population density of Padang City in 2020 and can accommodate 7.20% of the area with a tsunami vulnerability level in the very red zone (areas with a high level of vulnerability to tsunamis).